The Effect of Gross Domestic Product and Population Growth on CO2 Emissions in Indonesia: An Application of the Ant Colony Optimisation Algorithm and Cobb-Douglas Model - Sukono, Sukono; Albra, Wahyuddin; Zulham, T.; Majid, Iskandarsyah; Saputra, Jumadil; Subartini, Betty; Thalia, Friscila (International Journal of Energy Economics and Policy, 2019)
Gross Domestic Product (GDP) is one indicator for measuring a country’s economic growth. However, the increase in GDP and population growth are affecting CO2 emissions. This study analyses the effects of GDP and population density on CO2 emissions in Indonesia. To this end, it used the Cobb-Douglas model, and parameter estimation using Ant Colony Optimisation algorithm. The analysis of the results reveals that GDP and population density influence CO2 emissions in Indonesia significantly, and significantly follows the Cobb-Douglas model with increasing return to scale characteristics. Thus, an increase in GDP and population density will lead to increased CO2 emissions in Indonesia. Keywords: Economic Growth, Gross Domestic Product, Population Growth, CO2 Emission, Ant Colony Optimisation Algorithm, Cobb-Douglas model JEL Classifications: C61, O47, O150, Q530 DOI: https://doi.org/10.32479/ijeep.8011